Learning Chemistry in English: The Relationship between Language Skills and Learning Outcomes - Rudi Firmayanto; Leny Heliawati; Bibin Rubini (Universitas Islam Negeri Raden Intan Lampung, 2020)
The study aims to analyze the relationship between English language skills and the students' learning outcomes in chemistry learning that uses English as the medium of instruction (EMI). This qualitative descriptive study was conducted on 40 high school students. Data is collected and analyzed in the form of the test result of the language skills and learning outcomes. The results for students' language skills: 75 % of students are at level A2 (primary user), 15 % are at level B1 (intermediate), 5 % are at level B2 (upper-intermediate), and 5 % are at level C1 (advance/proficient user). The students' chemistry learning results are averagely low, i.e., 70 % of students gained a score under 75 as the minimum criteria of standard learning,  only 30 % of students reached the score above the KKM (Criteria of Minimum Competency). The conclusion of this research is that there is a relationship between language skills and chemistry learning outcomes. Learning chemistry in English has not given good results for students' learning outcomes. Therefore, the demands of learning in English need to be supported by good language skills to understand the learning content.